CAR-T-cell-based immunotherapies in hemato-oncology: Focus on use in clinical routine CAR-T-Zell-basierte Immuntherapien in der Hämatoonkologie: Fokus auf den Einsatz in der klinischen Routine - Steinhardt, M. J.; Reinhardt, L.; Luu, M.; Danhof, S.; Hudecek, M. (Die Onkologie, 2023)
Chimeric antigen receptor (CAR)-T-cell-based therapies are a modern pillar in immunotherapy. They show promising response rates in relapsed/refractory B and plasma cell malignancies. Cancer recurrence after initial response and lack of efficacy against solid tumors are key challenges for health care providers, patients, and researchers in the CAR-T cell therapy. Another problem is the currently limited production capacity. Here, we discuss the challenges for this promising therapy as well as possible solutions and recent innovations. With increased use of CAR-T cell therapy, there is growing experience in recognizing and treating acute and chronic side effects. We provide an update on clinical routine and patient management before, during, and after CAR‑T cell therapy.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Leukemia; Lymphoma; Multiple myeloma; Receptors; chimeric antigen; Solid tumors